A HISTORY OF UNITED STATES ARTISTIC GYMNASTICS - Abie Grossfeld (Science of Gymnastics Journal)
“A History of United States Gymnastics,” by Abie Grossfeld, covers the development and accomplishments of U.S. gymnastics through the years, starting with the organizations and the individual pioneers who introduced and helped spread gymnastics across the U.S. The contributions, to U.S. gymnastics, of the various organizations – Turnvereins, Sokols, YMCAs, athletic clubs, colleges, and high schools - are explained. In addition are the roles that the NCAA and AAU had in U.S. gymnastics development. Presented are the nature of and the participation in the various past and present gymnastics events (apparatus). Listed are skills that were initially performed by U.S. gymnasts for each event, and the notable accomplishments of U.S. gymnastics luminaries. How American gymnasts fared in international competition, with special performances, through the years, starting with the 1904 Olympic Games up to the 2009 World Championships. Lists for U.S. gymnastics medal winners are provided for the U.S. Olympic Games, World Gymnastics Championships, World University Games and Pan American Games.